The Impact of Body Mass Index and Body Composition on Cardiac Autonomic Function in Young Adult Saudi Females - Gehan I. El-Salamony,; Sahar M. El-Agaty,; Basma M. Zawawi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This work was carried out to elucidate the impact of body mass index, body fat and its distribution, body water and body muscles on the cardiac autonomic control in healthy young adult female students at King Abdulaziz University during 2012. Heart rate variability parameters were correlated with anthropometric measurements and body composition (fat, muscles and water). Time domain and frequency domain parameters of heart rate variability were decreased as the body mass index and percentage of body fat increase. In addition, these anthropometric measurements revealed significant positive correlations with the ratio of low frequency to high frequency components, pointing to the adverse effect of body fat on sympathovagal balance. Waist circumference, an index of central obesity, was negatively correlated with the number of pairs of successive NNs that differ by more than 50 ms. The percentage of body water showed a significant negative correlation with low frequency to high frequency ratio. Also, body muscles percentage represented a negative correlation with this ratio, though insignificant. Therefore, this study concluded that high indices of overall and central obesity seem to impair cardiac autonomic balance in healthy adult females. Additionally, increased body water and lean body mass are associated with favorable effects on cardiac autonomic function.